2017
DOI: 10.1007/s10853-017-1057-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-like cell responses to silicate ions released from 45S5-type bioactive glass and siloxane-doped vaterite

Abstract: Purpose: Silicate ions released from bioactive glasses and ceramics have been reported to stimulate osteogenic cell functions. Here, we evaluated osteoblast-like cell reactions to silicate ions released from two different types of materials, 45S5 bioactive glass (BG) and siloxane-doped vaterite (SiV), to investigate the influence of the ionic structure of silicate ions on osteoblast-like cell properties.Methods: BG and SiV powders were prepared by using melt-quenching and carbonation methods, respectively. Ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…After 3 d, the silicate ion release was almost controlled. Obata et al [31] reported that when an appropriate amount of silicate ions was supplied only at the initial stages of cell culture, mineralization could be enhanced. Such phenomena are caused by the formation of pathways for ion release, originating from the water uptake ability of the polymer.…”
Section: Ion Release Behaviormentioning
confidence: 99%
“…After 3 d, the silicate ion release was almost controlled. Obata et al [31] reported that when an appropriate amount of silicate ions was supplied only at the initial stages of cell culture, mineralization could be enhanced. Such phenomena are caused by the formation of pathways for ion release, originating from the water uptake ability of the polymer.…”
Section: Ion Release Behaviormentioning
confidence: 99%
“…For example, novel bioactive silicate glasses (both melt-derived and solgel produced) incorporating B [7,8], bivalent ions such as Mg, Zn, Sr and Cu [9], Li [10], Ce [11], Sr [12,13], Cu, Zn [14], Mn [15], are discussed. The release of ''classical'' ions in bioactive glasses, namely Si, Ca, P, is the subject of the studies of Houreh et al [16] and Obata et al [17] in the context of dental pulp stem cells and osteoblast cell responses, respectively. Moreover novel Cu-and Fe-doped phosphate glasses and sol-gel-derived borate bioactive glasses are the subject of the contributions Mishra et al [18] and Lepry et al [19], respectively.…”
Section: ó Springer Science+businessmentioning
confidence: 99%
“…Aminopropyltriethoxysilane (APTES) is the Si source used in SiV, and the Si ions released by SiV have a structure different from that of Si ions released by conventional bioactive glasses, such as 45S5 bioglass. Although osteoblast‐like cells have demonstrated differences between the responses to Si ions released from SiV and 45S5 bioglass as well as different Si dose dependence, Si ions from both sources enhance cell mineralization …”
Section: Introductionmentioning
confidence: 99%
“…Most bioactive glasses release several types of inorganic ions that form a part of their chemical compositions. For example, 45S5 bioglass releases Si, Ca, sodium (Na), and phosphate (P) ions on dissolution, of which Ca, Na, and P ions are naturally present and perform essential functions in body fluids . The dissolution product of 45S5 bioglass stimulates several cell functions, and the stimulation processes and their dose dependence to various ions have been revealed in many studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation